Malaysian Film Industry in transformation:challenges and potential - Jamaluddin Aziz,; Hasrul Hashim,; Faridah Ibrahim, (Universiti Kebangsaan Malaysian, 2014)
The aim of this paper is to discuss the challenges and potentials of the Malaysian film industry from the perspective of the industry players such as filmmakers and producers. Malaysian film industry is a relatively small industry that caters to the need of a population of only about 27.5 millions. In the context of globalization, this small local market presents a challenge for the government in promoting the industry as part of a creative industry with great economic potential. With the influx of films from abroad, especially from Hollywood, the industry is struggling to the hilt to survive, as the bigger portion of the audience prefers Hollywood to local productions. For the government, one way of achieving this is to promote local films at the international level. To understand this situation from inside the industry itself, this paper, using data from in-depth interviews with 10 industry players, discusses the challenges faced by the respondents and how they perceive the potential of Malaysian films to travel globally.